A Comparative Evaluation of Efficacy of Tacrolimus and Triamcinolone Acetonide in the Management of Symptomatic Oral Lichen Planus - Y M Swarna; I M Ali; Rajeshwari G Annigeri; G M Devarasa (Wolters Kluwer Medknow Publications, 2011)
Background and objectives: Oral lichen planus (OLP) is a relatively common, chronic inflammatory condition, which frequently present with burning sensation. Only symptomatic OLP requires treatment and efforts are made in a continued searching for novel therapies for symptomatic OLP. Therefore, this study was aimed to compare the efficacy of treatment with topical tacrolimus ointment with that of triamcinolone acetonide ointment in subjects with symptomatic OLP. Materials and methods: This prospective randomized comparative study, included 30 symptomatic OLP subjects, divided into two groups as group A and group B to receive topical tacrolimus 0.03% ointment and triamcinolone acetonide 0.1 % ointment application respectively, twice daily for four consecutive weeks. Burning sensation using visual analog scale (VAS), overall treatment response using Tel Aviv-San Francisco scale was recorded at every visit. The data obtained was analyzed statistically using Wilcoxson Rank Test, Mann Whitney and Fischer's Exact Test. Results: Subjects in both the groups showed a significant reduction in burning sensation; however, it was higher (98%) in tacrolimus group than in the triamcinolone acetonide group (72%). The overall treatment response was significantly better in tacrolimus group. Interpretation and conclusion Topical tacrolimus 0.03% ointment induced better initial therapeutic response than triamcinolone acetonide 0.1 % ointment. However, relapses occurred in two subjects in group 'A' and three subjects in group 'B' after the cessation of the respective treatments. Nevertheless, at present topical tacrolimus may be a valuable addition to the already existing therapeutic modalities for treating subjects with OLP.